Analisis Yuridis Gugatan Perbuatan Melawan Hukum atas Anomali Sistem Elektronik Perbankan (Studi Putusan MA Nomor 1281 K/Pdt/2017) - Theodore Christian Nathanael Nababan; Taufiqur Rahman Andi Fitra (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The provision of bank credit to the public is a strategic activity that contributes significantly to national economic growth; however, it entails substantial legal complexities in practice. This study aims to analyze the civil law aspects of credit allocation, including the validity of credit agreements, the prudential principle, the role of collateral, and dispute resolution arising from default. A normative legal research methodology was employed to examine legal documents, statutory regulations, and academic literature related to banking practices. The findings reveal that the use of standard form contracts often places debtors in a weaker bargaining position, creating a potential for legal imbalance. Furthermore, the application of the prudential principle and the execution of collateral remain inconsistent, thereby increasing the risk of non-performing loans. These findings underscore the need to strengthen regulations governing credit agreements and enhance legal literacy among debtors to ensure a fair and balanced creditor-debtor relationship within Indonesia’s civil law framework.